Political Accountability and the Size of Government: Theory and Cross-Country Evidence. - David Dreyer Lassen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2000)
This paper explores the effect of political accountability on the size of the public sector in a principal-agent model of democratic government. Political accountability is the degree to which the electorate can control politicians through elections, and emphasis is put on the roles of transparency and political contestability. Increasing transparency and political contestability increases the control of politicians, which makes public goods provision more attractive to voters, increasing the size of government. The prediction of the model is strongly supported by robust empirical evidence from a cross section of 62 democratic countries in 1995.
Keywords: 330